1965
DOI: 10.3382/ps.0440437
|View full text |Cite
|
Sign up to set email alerts
|

Gelation of Frozen-Defrosted Egg Yolk as Affected by Selected Additives: Viscosity and Electrophoretic Findings

Abstract: INSECTICIDE RESIDUES437 producers being careful in selecting and buting feeds that are free of chlorinated insecticide residues, for use in their poultry operations. SUMMARY 1. Supplying the equivalent of 0.1 to 0.15 p.p.m. of lindane, dieldrin, heptachlor and DDT in the feed to laying hens in capsule form for 14 days resulted in some residues in chicken tissues which disappeared rapidly.2. Supplying the equivalent of 10 to 15 p.p.m. of the same insecticides in the feed for 5 days resulted in significant resid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

1967
1967
2010
2010

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 16 publications
2
14
0
Order By: Relevance
“…Viscosity of egg yolk increases with addition of salt (NaCl) (Jordan and Whitlock, 1955;Meyer and Woodburn, 1965), but degree of gelation due to freezing decreases as concentration of NaCl is increased (Powrie et al, 1963). Palmer et al (1969a, b) showed that pasteurization did not change the effect of frozen storage on 10% salted egg yolk, but it caused a slightly increased viscosity in unfrozen salted yolk.…”
Section: Introductionmentioning
confidence: 99%
“…Viscosity of egg yolk increases with addition of salt (NaCl) (Jordan and Whitlock, 1955;Meyer and Woodburn, 1965), but degree of gelation due to freezing decreases as concentration of NaCl is increased (Powrie et al, 1963). Palmer et al (1969a, b) showed that pasteurization did not change the effect of frozen storage on 10% salted egg yolk, but it caused a slightly increased viscosity in unfrozen salted yolk.…”
Section: Introductionmentioning
confidence: 99%
“…Kline et al (1965) noted that with a rise in yolk solids from 50.8 to 53.2% the viscosity increased markedly from 782 to 1926 cps at 2S°C. The viscosity of fresh yolk with a percent solids content of about 52.7 was estimated by Meyer and Woodburn (1965) to be around 27 poises, whereas yolk with 50% solids (from stored eggs) had a viscosity of approximately 9 poises. According to Payawal et al (1946) the viscosity of native yolk with a solids content of 50.5 to 51% was about 800 cps at 2S'C.…”
Section: Introductionmentioning
confidence: 99%
“…dilutions were liquid probably due to dispersion of yolk particles. The addition of 5.5 ml distilled water per 100 g of yolk was found by Meyer and Woodburn (1965) These results indicated that gelation of yolk was a function of freezing rate up to a certain point.…”
Section: Gelation Of Egg Tolkmentioning
confidence: 62%
“…No similar effect on the apparent viscosity of unfrozen yolk was noted for fructose. Jordan and Whitlock (1955), Karion and Stadelman (1958), and Meyer and Woodburn (1965) also reported that bhe apparent viscosity of unfrozen yolk was increased by the addition of sodium chloride.…”
mentioning
confidence: 99%